PERANCANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBANTUAN GEOGEBRA PADA SUB POKOK BAHASAN NILAI-NILAI STASIONER DI KELAS XI IPA DENGAN PENDEKATAN KLASIKAL - Iin Nur Indahsari (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2016)
Mathematics is one science that has many benefits in life, but unfortunately, some who think that mathematics is a difficult subject, especially difficult to receive materials in learning. From the above problems, researchers are interested in developing a learning device that aided GeoGebra on sub subject stationary values ​​in grade XI with a classical approach. Learning software design is a process of achieving the learning objectives, along with the evaluation process and the design should be in accordance with the model development and meet the criteria. The model used is the development of devices Sugiyono development model that has been modified. Learning tools are developed in accordance with the criteria of development proposed by Nieveen ie, valid, practical, and effective. Criterion validity was measured based on the process and results of the validation, practicality criteria measured through observation of the teacher's ability to manage learning, and effectiveness criteria measured through observation of activities of students and teachers during the learning process and learning achievement test. The experiment was conducted in SMA Negeri 1 Madiun with test subjects in class XI IPA 5. From this research, the findings, namely: the overall learning device comprising (RPP, BPG, BKS, Slide Learning, and THB) are valid and ready for use on the learning process, the value of teacher's ability to manage learning in the category quite well, the activity of students and teachers during the learning process is the active criteria, but in the classical learning completeness students do not meet the criteria. Thus the process of software development is done by Sugiyono development strategy that has been modified and developed learning tools have valid criteria, practical, but not effective.Keywords: Design, Mathematics Learning Assisted GeoGebra, Classical approaches.